Dibenzofuran-based iridium complexes as green emitters: Realizing PhOLEDs with high power efficiency and extremely low efficiency roll-off. (February 2020) - Fang, Daqi; Sun, Yue; Chen, Youquan; Fu, Tianchen; Ali, Muhammad Umair; He, Yaowu; Miao, Jingsheng; Yan, Chaoyi; Meng, Hong
Abstract: In this work, a series of novel iridium (III) cyclometallated complexes BF–Ir1, BF–Ir2 and BF–Ir3 is developed by introducing a dibenzofuran moiety into the main ligand. The photophysical, thermal, and electroluminescent properties of these iridium (III) complexes are systematically investigated. Notably, the phosphorescent organic light-emitting diodes (PhOLEDs) with BF–Ir1, BF–Ir2 and BF–Ir3 as the green emitters displayed the maximum EQEs of 15.1%, 23.7% and 21.5%, respectively. In addition, an impressively high PE up to 96.8 l m W −1 is achieved in the device based on BF–Ir3 . When the luminance reached 1000 and 10000 cd m −2, the corresponding EQE values of BF–Ir3 -based PhOLEDs could be maintained at 20.7% and 18.5%. These results clearly demonstrate that dibenzofuran-based iridium (III) complexes have great potential for their application as green emitters in PhOLEDs to realize both high EQE and PE as well as low efficiency roll-off. Highlights: A series of novel iridium (III) complexes with dibenzofuran moiety are synthesized through a facile synthetic route. All iridium (III) complexes displayed great thermal stability and high photoluminescence quantum yields. PhOLEDs with these complexes as green emitters showed the maximum EQE of 23.7% and impressively high PE of 96.7 l m W −1 . Moreover, our fabricated PhOLEDs showed extremely low efficiency roll-off at high luminance.